2020
DOI: 10.3390/brainsci10010024
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrent Arterial Ischemic Stroke in Children and Young Adults

Abstract: Arterial ischemic stroke (AIS) experienced at a young age is undoubtedly a serious medical problem. AIS very rarely occurs at a developmental age, whereas in young adults, it occurs with a higher frequency. The etiologic mechanisms of AIS occurring in childhood and adulthood differ. However, for both age populations, neurological consequences of AIS, including post-stroke seizures, motor disability, and recurrence of the disease, are connected to many years of care, rehabilitation, and treatment. Recurrent str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 98 publications
0
20
0
Order By: Relevance
“…Based on recent studies, hypertension was considered a risk factor of recurrent stroke in adults. 4,7 Indeed, Pezzini et al 6 reported that blood pressure increases the risk of recurrent stroke by 2-fold (HR: 2.36). Schneider et al 12 demonstrated that 69% of recurrent stroke patients in Estonia have hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent studies, hypertension was considered a risk factor of recurrent stroke in adults. 4,7 Indeed, Pezzini et al 6 reported that blood pressure increases the risk of recurrent stroke by 2-fold (HR: 2.36). Schneider et al 12 demonstrated that 69% of recurrent stroke patients in Estonia have hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of adult patients with IS, 10–15% of all strokes were experienced by so-called “young stroke” adults. 11 Nevertheless, heterogeneity in “young stroke” definition lead to a wide range of stroke incidence in this patient population. 11 Emerging data has elevated public health concerns about the increasing prevalence of vascular risk factors in young adults, and their potential role in increasing the risk of IS, and stroke recurrence.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Nevertheless, heterogeneity in “young stroke” definition lead to a wide range of stroke incidence in this patient population. 11 Emerging data has elevated public health concerns about the increasing prevalence of vascular risk factors in young adults, and their potential role in increasing the risk of IS, and stroke recurrence. 12 Although the global risk of mortality is low, stroke in young adults has severe implications.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric populations, the risk factors associated with AIS are cardiac disorders, including congenital heart disease, infections, head and neck trauma, prothrombotic disorders, sickle cell disease, cancer, genetic disorders, and inborn errors of metabolism, as well as autoimmune and inflammatory states [8]. However, the most important risk factors for AIS in pediatric populations are arteriopathies, congenital and acquired cardiac diseases, thrombophilia, and prothrombotic disorders [9]. Furthermore, in the literature, risk factors for recurrent AIS were also described.…”
Section: Arterial Ischemic Stroke In Childrenmentioning
confidence: 99%